2008
DOI: 10.1063/1.2955832
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution in H ion induced splitting of freestanding GaN

Abstract: We investigated the microstructural transformations during hydrogen ion-induced splitting of GaN thin layers. Cross-sectional transmission electron microscopy and positron annihilation spectroscopy data show that the implanted region is decorated with a high density of 1-2 nm bubbles resulting from vacancy clustering during implantation. These nanobubbles persist up to 450°C. Ion channeling data show a strong dechanneling enhancement in this temperature range tentatively attributed to strain-induced lattice di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
2
33
1
Order By: Relevance
“…Positron annihilation is a powerful technique to evaluate vacancy-type defects in semiconductors, 16,17 and defects in group-III nitrides have been successfully investigated using this method. [18][19][20][21][22][23][24] In this study, we used a monoenergetic positron beam to probe native vacancies in Al 0.1 Ga 0.9 N layers grown on Si substrates. We showed that the obtained results provided additional insights to explain the change in the leakage blocking capability of these layers.…”
Section: Introductionmentioning
confidence: 99%
“…Positron annihilation is a powerful technique to evaluate vacancy-type defects in semiconductors, 16,17 and defects in group-III nitrides have been successfully investigated using this method. [18][19][20][21][22][23][24] In this study, we used a monoenergetic positron beam to probe native vacancies in Al 0.1 Ga 0.9 N layers grown on Si substrates. We showed that the obtained results provided additional insights to explain the change in the leakage blocking capability of these layers.…”
Section: Introductionmentioning
confidence: 99%
“…All these parameters strongly depend on the type of semiconductor materials used for splitting. In contrast to the cases of Si, SiC, Ge, GaAs and InP, only a few studies of H-implantation-induced GaN layer splitting were reported [2][3][4][5][6][7][8]. Tong et al [9] reported that blister formation and layer splitting have the same activation energy, indicating that formation of optically detectable surface blisters is regarded as onset of microcrack formation.…”
Section: Introductionmentioning
confidence: 92%
“…Positron annihilation, a powerful technique for evaluating vacancy-type defects in semiconductors, 17,18 has been used to investigate defects in group-III nitrides. [19][20][21][22][23][24][25][26] In the present study, we used a monoenergetic positron beam to probe native vacancies in Mg-doped GaN grown by NH 3 -based MBE.…”
Section: à3mentioning
confidence: 99%